Eyes on me - Cate, Sara (Cate, Sara. Salacious Players' Club, 2023)
"I'm a voyeur--it means I like to watch. And in my line of work, that's a gift. As one of the four owners of the Salacious Players' Club, I'm comfortable on the sidelines. This is what I was made to do, and I work better alone. Until the day I stumble on a certain cam girl app and find myself watching the one person I should never have watched--my step-sister. There are three big problems with this. One, Mia and I can't stand each other. Two, she has no idea I'm the man on the other end of the video. And three...I'm hooked--on the app and on her. Now, Mia has me wanting and doing things I said I'd never do again, like opening up and getting attached. I'm falling for her, but she's falling for the mystery man I'm pretending to be. If I'm going to make this right, then I have to do more than just watch. But how far will I go to keep her eyes on me?" --Back cover.